Distributed quality of service provision using coalitions and the Nash bargaining solution. Issue 4 (1st March 2013) - Vatsikas, Stefanos; Armour, Simon; Lewis, Tim; De Vos, Marina
Abstract : A new scheduler with the capability for distributed quality of service (QoS) provision is presented. Based on the game‐theoretic concepts of coalition formation and bargaining, this scheduler follows a hybrid approach to allocate subcarriers and to satisfy the minimum rate requirement of the wireless users. In the first part of the allocation process, a greedy approach is used to provide users minimum data rate requirements. Then, in the game‐theoretic part of the process, the remaining resources are split in a fair manner between the users by forming dynamically sized coalitions and by allowing users to bargain with each other, using the Nash bargaining solution. The novelty of this approach lies in the fact that it allows the distributed, partly‐cooperative provision of QoS in a multiuser wireless channel. This new scheduler is compared against the proportional fair and greedy schedulers and the simulation results indicate that the proposed scheduler offers better QoS outage performance than others. It also offers fairness and sum rate that are comparable to the PF scheduler, while the comparison with the Greedy scheduler indicates significantly better fairness, but lower sum rate.